Characterization of malunggay (Moringa oleifera L.) glucosinolates - Malabed, Raymond S. (Animo Repository, 2010)
Glucosinolate and their corresponding hydrolytic products have been found to exhibit chemopreventive properties. Malunggay (Moringa oleifera L.) was found to contain a predominant glucosinolate - glucomoringin. In this study, methanol extracts will be prepared from freeze-dried samples of raw and boiled malunggay leaves and seeds which will be immediately followed by desulfation using DEAE Sephadex A-25 resin. The desulfated glucosinolate content of the vegetable samples will be analyzed and compared using HPLC, GC and LC-MS. Powdered samples of raw and boiled malunggay will be defatted using n-hexane and will be allowed to undergo hydrolysis with and without the presence of myrosinase. Air-dried samples will be extracted with DCM and will be subjected to GC-MS and GC-FID analyses. Malunggay juice, powdered samples and DCM extracts will also be subjected to Comet assay to determine whether the samples have potent anti-cancer activities.